ENHANCING STUDENTS’ LEARNING OUTCOMES: BITS AND PIECES GAME - Sriati Usman; Budi Budi; Abdul Kamaruddin; Ayu Faradila (IJEE (Indonesian Journal of English Education), 2023)
ABSTRACTThis research analyzes the implementation of the "bits and pieces" game on students' learning outcomes in writing English descriptive texts. A quasi-experimental design with Junior High School students as the population and a cluster random sampling technique used to draw the sample. Furthermore, two groups were administered pre- and post-test to collect the data. According to the data analysis, a noteworthy disparity existed in the post-test outcomes between the two groups. The experimental group had an average score of 86.60, whereas the control group had 62.43 score. By setting a significance level of 0.05 and degree of freedom (df) of 40 (21+21-2), the t-test demonstrated that the calculated t-value (6.487) surpassed the critical value (1.684), thereby indicating the acceptance of the research hypothesis. This implied that bits and pieces games have an effect on enhancing students’ learning outcomes. Therefore, the game can be a great contribution for English teachers in teaching English descriptive text, in terms of improving content, mechanics, organization, sentence structure, and grammar. ABSTRAKPenelitian ini menganalisis implementasi permainan bits dan pieces terhadap hasil belajar siswa dalam menulis teks deskriptif dalam bahasa Inggris. Desain penelitian yang digunakan adalah eksperimen semu. Populasinya siswa SMP dan teknik pengambilan sampel melalui cluster random sampling. Data diambil dari hasil pre- dan post-test pada kelompok kontrol dan eksperimen yang menunjukkan terdapat pengaruh atau peningkatan pada kelompok kontrol dan eksperimen. Nilai rata-rata dari post-test pada kelompok eksperimen sebesar 86.60 dan kelompok kontrol sebesar 62.43 dengan menerapkan tingkat signifikansi 0.05 dan derajat kebebasan (df) 40 (21+21-2), hal ini menunjukkan nilai t-hitung (6.487) lebih besar dari nilai t- tabel (1.684) yang bermakna bahwa hipotesa penelitian ini diterima. Dengan demikian permainan bits dan pieces berpengaruh terhadap peningkatan hasil belajar siswa dalam menulis teks deskriptif. Oleh karena itu, hasil penelitian ini sangat berkontribusi kepada guru Bahasa Inggris yang mengajarkan keterampilan menulis teks deskriptif Bahasa Inggris yang berkaitan dengan peningkatan isi, penggunaan tanda baca, huruf besar dan kecil, pengorganizatian teks deskriptif, dan aturan kata dalam kalimat.How to Cite: Hairul, M.A., Nurhayati. (2023). Exploring Teacher Educators’ Understanding of Critical Pedagogy and its Implementation in the English Reading Class. IJEE (Indonesian Journal of English Education), 10(1), 207-220. doi:10.15408/ijee.v10i1.32312